ANALYSIS OF THE EFFECT OF EXCHANGE RATES, INDONESIAN COFFEE PRODUCTION AND INTERNATIONAL COFFEE PRICE ON COFFEE EXPORT VOLUME IN INDONESIA - Oktoriza, Linda Ayu (Universitas Dian Nuswantoro, 2023)
The aim of this study was to determine the effect of exchange rates, production and international prices jointly on export volumes and the effect of exchange rates, production and international prices partially on export volumes. This research is a type of explanatory research research with a quantitative approach. The variables used in this study are the exchange rate, Indonesian coffee production and international coffee prices as the independent variables, and the volume of Indonesian coffee exports as the dependent variable.This study uses secondary data using time series ( time series ) during the period 2018 to 2022 with a total of 30 data taken from 6 countries, each country taken 5 years. The data analysis method is multiple linear regression analysis.The results of multiple linear regression analysis show that there is a joint effect between the variables of exchange rates, production, and international prices on export volume, there is no partial effect between the variables of exchange rates and production on export volume, and there is a partial effect between international prices and export volume.